1990
DOI: 10.1104/pp.93.4.1433
|View full text |Cite
|
Sign up to set email alerts
|

Response of the Photosynthetic Apparatus in Dunaliella salina (Green Algae) to Irradiance Stress

Abstract: The response of the photosynthetic apparatus in the green alga Dunaliella salina, to irradiance stress was investigated. Cells were grown under physiological conditions at 500 millimoles per square meter per second (control) and under irradiance-stress conditions at 1700 millimoles per square meter per second incident intensity (high light, HL). In control cells, the light-harvesting antenna of photosystem I (PSI) contained 210 chlorophyll a/b molecules. It was reduced to 105 chlorophyll a/b in HL-grown cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
117
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(129 citation statements)
references
References 30 publications
7
117
0
2
Order By: Relevance
“…Exposing the algal cells to the elevated salt concentration resulted in a decline in the D1 protein. This finding is in line with the well-documented role of the D1 protein in down-regulating the activity of PSII (Smith et al, 1990;Harrison et al, 1992;Shipton & Barber, 1994;Komenda & Masojidek, 1995;Zeng & Vonshak, 1998;Sudhir et al, 2005). The decrease in the level of the protein in response to high salt was much higher in wild-type cells.…”
Section: Discussionsupporting
confidence: 76%
“…Exposing the algal cells to the elevated salt concentration resulted in a decline in the D1 protein. This finding is in line with the well-documented role of the D1 protein in down-regulating the activity of PSII (Smith et al, 1990;Harrison et al, 1992;Shipton & Barber, 1994;Komenda & Masojidek, 1995;Zeng & Vonshak, 1998;Sudhir et al, 2005). The decrease in the level of the protein in response to high salt was much higher in wild-type cells.…”
Section: Discussionsupporting
confidence: 76%
“…However, recently, through a study in which Cklorella vulgaris grown under continuous light at 5"C/150 pmol m-'s-' was compared to C. vulgaris grown at 27"C/150 pmol m-'s-', we concluded that this assumption is invalid (Maxwell et al, 1994). Based on published data concerning acclimation of algae to high irradiance (Sukenik et al, 1988;Senge and Senger, 1990;Smith et al, 1990;Harrison et al, 1992), we suggested that growth of C. vulgaris at low temperature mimics high-light acclimation even though C. vulgaris was grown at a low to moderate irradiance of 150 pmol m-'s-' (Maxwell et al, 1994). For example, compared to growth at 27"C/150 pmol m-' s-', Cklorella grown at 5"C/150 pmol m-'s-' exhibited a doubling in the light-saturated rate of C0,-saturated O, evolution, a 2-fold increase in the ratio of Chl a / b , a 5-fold lower total Chl per cell, decreased abundance of LHCII polypeptides, and increased total xanthophyll content (Maxwell et al, 1994).…”
mentioning
confidence: 96%
“…The concentration of the photosystems in thylakoid membranes was estimated spectrophotometrically from the amplitude of the light-minus-dark absorbance difference signal at 700 nm (P700) for PSI, and 320 nm (Q A ) for PSII [45,46]. The functional light-harvesting Chl antenna size of PSI and PSII was measured from the kinetics of P700 photooxidation and Q A photo-reduction, respectively [47].…”
Section: (G) Spectrophotometric Analysesmentioning
confidence: 99%
“…Following sonication, the crude cell extract was incubated in the presence of solubilization buffer [46]. Gel lanes were loaded with an equal amount of Chl, in the range of 1 -2 nmol Chl, as indicated.…”
Section: (G) Spectrophotometric Analysesmentioning
confidence: 99%